Particle hydrodynamic simulation of thrombus formation using velocity decay factor. (August 2021) - Wang, Fei; Xu, Songhua; Jiang, Dazhi; Zhao, Baoquan; Dong, Xiaoqiang; Zhou, Teng; Luo, Xiaonan
Highlights: We integrate the physiological thrombosis principle into the blood simulation process and propose a thrombosis simulation method based on the velocity decay factor. The proposed method overcomes the limitations of traditional simulation models such as the high computational complexity of traditional Euler-based methods and the missing of physiological characteristic simulation in SPH methods. The proposed direct position correction method resolves the problem of particle degradation and thus yields more realistic visual effect of thrombus simulation. The proposed model can be used to simulate thrombus formation and its interaction with blood flow both effectively and efficiently. Abstract: Background and objective: Thrombus simulation plays an important role in many specialist areas in the field of medicine such as surgical education and training, clinical diagnosis and prediction, treatment planning, etc. Although a considerable number of methods have been developed to simulate various kinds of fluid flows, it remains a non-trivial task to effectively simulate thrombus because of its unique physiological properties in contrast to other types of fluids. To tackle this issue, this study introduces a novel method to model the formation mechanism of thrombus and its interaction with blood flow. Methods: The proposed method for thrombus formation simulation mainly consists of three steps. First, we formulate the formation of thrombus as a particle-based model and obtain the fibrin concentration of the particles with a discretized form of the convection-diffusion-reaction equation; then, we calculate the velocity decay factor using the obtained fibrin concentration. Finally, the formation of thrombus can be simulated by applying the velocity decay factor on particles. Results: We carried out extensive experiments under different settings to verify the efficacy of the proposed method. The experimental results demonstrate that our method can yield more realistic simulation of thrombus and is superior to peer method in terms of computational efficiency, maintaining the stability of the dynamic particle motion, and preventing particle penetration at the boundary. Conclusion: The proposed method can simulate the formation mechanism of thrombus and the interaction between blood flow and thrombus both efficiently and effectively.